I hear you feel confident - Bricker Adam Michael (The Philosophical Quarterly, 2022)
Here I explore a new line of evidence for belief–credence dualism, the thesis that beliefs and credences are distinct and equally fundamental types of mental states. Despite considerable recent disagreement over this thesis, little attention has been paid in philosophy to differences in how our mindreading systems represent the beliefs and credences of others. Fascinatingly, the systems we rely on to accurately and efficiently track others’ mental states appear to function like belief–credence dualists: Credence is tracked like an emotional state, composed of both representational and affective content, whereas belief is tracked like a bare representational state with no affective component. I argue on a preliminary basis that, in this particular case, the mechanics of mentalizing likely pick out a genuine affective dimension to credence that is absent for belief, further strengthening the converging case for belief–credence dualism.